Risk factors of hearing defects and their relationship to the outcome of hearing screening among neonates - Hameed, Numan Nafie; Malih, Mokhalad Ghazi (Journal of the Faculty of Medicine Baghdad, 2019)
Background: Increased exposure to risk factors of hearing loss leads to a high susceptibility to deafness among neonates admitted to neonatal care units in developing countries. Objective: This article aims to study the prevalence of risk factors for neonatal hearing defect and determine their effect on the result of transient evoked otoacoustic emissions hearing test ( TEOAE). Methods: A longitudinal study was carried out for a period of one year from 1st October, 2016 to 30 th September, 2017 in the CWTH, Medical city, Baghdad, Iraq Demographic characteristics and certain risk factors were recorded for screened neonates. TEOAE test was done and if they failed to pass two steps, they were referred to autom ated auditory brainstem - response (AABR). Results: Out of 400 neonates, 342 (85.5%) passed from step 1TEOAE, while 58 (14.5%) were referred to step 2. From 58, 26 (44.8%) have passed step 2 and 32 (55.2%) not pass step 2 and were referred to AABR. From those 32 neonates with suspected hearing defect, NICU stay >7 days, ototoxic drugs >7days, use of ventilator >7 days, birth weight <1500gm, and craniofacial malformations were the main risk factors for hearing defects occurring in (90.6%), (90.6%), (59.4%), (40.6%), and (21.9%) respectively. Conclusions: Low birth weight , long intensive care stay, mechanical ventilation, drugs ototoxicity and craniofacial malformation of neonates are the main risk factors for failed TEOAE test